Consensus Control of the Multi-Agent Systems under both Disturbances and Noises (Journal of Nonlinear Modeling and Analysis, 2024)
Consensus tracking control problem of the multi-agent systemswith both noise and disturbances is studied in this paper. A robust adaptivecontrol scheme is designed according to Lyapunov stability theory. The maincontribution of this paper is that the consensus is realized in multi-agent systems with both noise and external disturbances. Numerical simulations arecarried out for the proposed scheme to demonstrate the effectiveness of thecontrol strategy proposed in this paper.